NÍVEIS DE COLINESTERASE EM TRABALHADORES RURAIS - Bellinaso, Maria d. L.; Guecheva, Temenouga N.; Santos, Greice F. F. d.; Rocha, João B. d.; Lima, Fernanda; Lima, Fernanda O. (Salão do Conhecimento, 2013)
Resumo